2021
DOI: 10.1021/acsami.1c12470
|View full text |Cite
|
Sign up to set email alerts
|

A Flexible Multi-Channel Hollow CNT/Carbon Nanofiber Composites with S/N Co-Doping for Sodium/Potassium Ion Energy Storage

Abstract: Carbon fibrous materials are the promising candidate for the anode of flexible sodium-ion batteries and potassium-ion batteries due to the structural advantages. However, the progress of mechanically robust anode materials with high electrochemical properties is still unsatisfactory for the flexible electrodes. Herein, the comprehensive design of the morphology with unique multi-channel hollow 1D/1D carbon nanotube/carbon nanofiber network and the lattice structure of carbon with S/N co-doping has been propose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 53 publications
0
32
0
Order By: Relevance
“…Zhang et al 179 synthesized a sandwich doped carbon nanotube @Nb 2 C (N‐CNT@Nb 2 C), which showed excellent electrochemical performance in LIBs, SIBs, and PIBs, such as stable cycle performance of more than 500 cycles. Chen et al 180 used S/N‐doped carbon nanotube/carbon nanofiber composites (CNT/SNCF) as negative electrode materials for SIBs and PIBs. Independent CNT/SNCF electrodes show high discharge capacity (274.1 and 212.5 mAh g −1 at 1 A g −1 after 1000 cycles, respectively) and excellent cycle stability (150.4 and 100.1 mAh g −1 after 5000 cycles at 5 A g −1 , respectively) and rate performance (109.3 mAh g −1 at 10 A g −1 and 108.7 mAh g −1 at 5 A g −1 , respectively) (Table 3).…”
Section: How To Design High‐performance Carbon‐negative Electrode Mat...mentioning
confidence: 99%
“…Zhang et al 179 synthesized a sandwich doped carbon nanotube @Nb 2 C (N‐CNT@Nb 2 C), which showed excellent electrochemical performance in LIBs, SIBs, and PIBs, such as stable cycle performance of more than 500 cycles. Chen et al 180 used S/N‐doped carbon nanotube/carbon nanofiber composites (CNT/SNCF) as negative electrode materials for SIBs and PIBs. Independent CNT/SNCF electrodes show high discharge capacity (274.1 and 212.5 mAh g −1 at 1 A g −1 after 1000 cycles, respectively) and excellent cycle stability (150.4 and 100.1 mAh g −1 after 5000 cycles at 5 A g −1 , respectively) and rate performance (109.3 mAh g −1 at 10 A g −1 and 108.7 mAh g −1 at 5 A g −1 , respectively) (Table 3).…”
Section: How To Design High‐performance Carbon‐negative Electrode Mat...mentioning
confidence: 99%
“…The P-N/UCS anode maintains a high specific capacity of 265.8 mAh g –1 after 2000 cycles at 1.0 A g –1 , and the corresponding average capacity attenuation is just 0.017% per cycle, which is considerably superior to those of most reported carbonaceous anodes (Figure e and Table S5). ,,,,,,, , The outstanding electrochemical performances of the P-N/UCS anode can be ascribed to the expanded interlayer distance, increased specific surface area, enhanced proportions of active N sites, and improved electronic conductivity based on the foregoing results, which can accelerate charge transport and K + diffusion kinetics through the extra P doping.…”
Section: Results and Discussionmentioning
confidence: 99%
“…In another study, Chen et al [ 68 ] investigated sulfur and nitrogen doping (S/N doping) impact on sodium‐ion batteries (NIBs) and potassium‐ion batteries (KIBs). The researchers designed a morphology with unique multi‐channel hollow 1D/1D carbon nanotube/carbon nanofiber network and lattice structure of carbon with S/N co‐doping (Figure 10b).…”
Section: Environmental Applicationsmentioning
confidence: 99%
“…Copyright 2021, Elsevier. b) Reproduced with permission [68]. Copyright 2021, American Chemical Society.…”
mentioning
confidence: 99%